PROMETHEE Method for Prioritization of Electrical Energy Audit In Industry - Agiantoro, Gellen Twin; Haddin, Muhamad; Marlyana, Novi (Journal La Multiapp, 2025)
The problem of electricity in industry is the increasing consumption of electrical energy which results in increasing electricity consumption costs. The solution is how to reduce electrical energy consumption in the factory. The first step is to conduct an electrical energy audit. This research discusses electrical energy audits in industry with the aim of providing recommendations for electrical energy efficiency. The model is determined as an industrial electrical system complete with an electrical loading system. Parameters determined: production machinery, lighting systems, office support equipment, clean water pumps and air conditioners. The PROMETHEE method was used for prioritization in selecting from several alternative energy-saving opportunities. The research stages began with an initial energy audit, calculation of energy consumption intensity (IKE), recapitulation of electrical energy consumption, determination of energy saving opportunities, and PROMETHEE calculation. The PROMETHEE method used with 3 (three) alternatives, namely energy saving opportunities at no cost, low costs energy saving opportunities and high costs energy saving opportunities. As the research object, only the production building at PT Hop Lun Indonesia (HLI), Semarang, Indonesia was determined. The results show that PROMETHEE can be used for electrical energy audits in industry. This is evidenced by the prioritisation of the best recommendation results from the three alternatives, namely the first order in low-cost energy saving opportunities by replacing the type of LED lamp that has the potential to save energy by 2,723 KWH/day, the second order of energy saving opportunities at no cost by socializing to all employees regarding energy savings and conducting periodic maintenance and the last order in high-cost energy saving opportunities by replacing AC Inverters which have the potential to save energy by 390 KWH/day and replacing motors on sewing machines using servo motors which have the potential to save energy by 38,286,400 KWH/day.